FROM STREET TRAFFIC TO SPACE: INNOVATIONS IN AUTONOMOUS VEHICLES - Korabayev, Sherzod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article explores the multifaceted innovations in autonomous vehicles (AVs), from the technological breakthroughs to societal impacts. It begins by highlighting how AVs have the potential to reshape transportation through automation, economic considerations, and shared mobility systems. Key technological advancements such as AI and machine learning are central to these transformations, enhancing vehicle safety and efficiency. The research also delves into urban planning and design challenges, addressing how cities need to adapt to AV integration. Ethical considerations, such as decision-making algorithms and moral implications, are also explored, emphasizing the interdisciplinary approach required. Additionally, advancements in aerial autonomous vehicles and UAVs are discussed, demonstrating the broad scope of autonomous technology across different transportation modes. Overall, this article provides a comprehensive analysis of AV innovations, from safety methodologies and AI frameworks to urban policy integration and the broader societal implications of autonomous systems.